2018
DOI: 10.1007/s12350-016-0638-5
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography (PET) utilizing Pittsburgh compound B (PIB) for detection of amyloid heart deposits in hereditary transthyretin amyloidosis (ATTR)

Abstract: PIB-PET, in contrast to DPD scintigraphy, has the potential to specifically identify cardiac amyloid depositions irrespective of amyloid fibril composition. The heart appears to be a target organ for amyloid deposition in ATTR amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 26 publications
0
52
1
2
Order By: Relevance
“…The absence of cardiac biopsy in these patients weakens the explanation of atrial infiltration, although the findings are consistent. However, a previous study from our group has shown the presence of amyloid infiltration in the heart of hereditary ATTR patients irrespectively of fibril type [18]. Our findings in hereditary ATTR cannot be automatically transferred to other types of amyloidosis.…”
Section: Limitationscontrasting
confidence: 52%
See 1 more Smart Citation
“…The absence of cardiac biopsy in these patients weakens the explanation of atrial infiltration, although the findings are consistent. However, a previous study from our group has shown the presence of amyloid infiltration in the heart of hereditary ATTR patients irrespectively of fibril type [18]. Our findings in hereditary ATTR cannot be automatically transferred to other types of amyloidosis.…”
Section: Limitationscontrasting
confidence: 52%
“…Despite LV involvement caused by amyloid depositions in the ATTR amyloidosis group [18], and irrespective of LV wall thickness, there was no significant difference in LA size when compared to the control group. This is an unexpected finding, since the LA, described as the "Cinderella of the left heart", is commonly enlarged in any form of LV disease [19,20].…”
Section: Data Interpretationmentioning
confidence: 67%
“…61 Marked elevations in T1 and extracellular volume 15 may be useful for diagnosis and monitoring response to therapy. 62 Encouraging results of treatment have been reported by Pilebro et al 63 using the tracer C-Pittsburgh compound B, which has been shown to detect cardiac amyloid by positron emission tomography (PET). 63 A definitive diagnosis of this condition still requires histological verification.…”
Section: Restrictive Cardiomyopathies Amyloid Cardiomyopathymentioning
confidence: 99%
“…These phenotypes have been associated with differences in amyloid fibril composition – type A (full length TTR and fragments) and type B (full length TTR) [55]. Pilebro et al investigated the role of 11 C–Pittsburgh compound B (PIB) to differentiate these subtypes of ATTR, and showed that global LV 11 C–PIB was higher in patients with Type B V30 M ATTR [56]. …”
Section: Pet-cmr In Heart Failurementioning
confidence: 99%